The Ethics of Blindness and the Postmodern Sublime: Levinas and Lyotard - M. .. Jay; A. V. Khazina; F. V. Nicolai (Вестник Мининского университета, 2017)
The excerpt below is the final chapter of M. Jay’s “Downcast Eyes: The Denigration of Vision in Twentieth-Century French Thought” concerning the long-term confrontment “iconoclasm vs visual imaginary” within modern European culture. According to the author the current discussion on postmodernism proves to be somewhat a small branch of this complex intellectual swim. This branch, so to say, seems to sway periodically from overwhelming voyeurism to the uncompromising iconoclasm. This is the context Jay brings in considering conceptions of E. Levinas and J.-F. Lyotard, two famous French thinkers who expressed those cardinal philosophical points. However, the author focuses not only on the distinction, but also on certain coherence, as well as the evolution of their views.